2009
DOI: 10.1111/j.1365-2109.2009.02167.x
|View full text |Cite
|
Sign up to set email alerts
|

Supplementary oxygen and temperature management during live transportation of greenlip abalone,Haliotis laevigata(Donovan, 1808)

Abstract: Live greenlip abalone, Haliotis laevigata, are highly valued in Australian export markets with demand increasingly being met with cultured stock. Live transportation of abalone requires the maintenance of favourable conditions within transport containers for periods exceeding 35 h. We examined the combined effects of temperature regulation (ice provision) and of supplemental oxygen (60% and 100% concentrations) on mortality rates of abalone over 7 days following a 35‐h simulated live‐transport experiment. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…These results suggest that extended periods of exposure at higher air temperature produce a stronger impact on abalone. These results are also consistent with the finding of Bubner and Harris (2005) in their study on simulated live transport of greenlip abalone ( H. laevigata ) over 35 h. They observed that the mortality levels (approximately 40%) in abalone packed with ice in air were significantly lower than those (approximately 90%) packed in air only, further showing that lower air temperatures can lessen the physiological impact of extended exposure periods on abalone.…”
Section: Discussionsupporting
confidence: 89%
“…These results suggest that extended periods of exposure at higher air temperature produce a stronger impact on abalone. These results are also consistent with the finding of Bubner and Harris (2005) in their study on simulated live transport of greenlip abalone ( H. laevigata ) over 35 h. They observed that the mortality levels (approximately 40%) in abalone packed with ice in air were significantly lower than those (approximately 90%) packed in air only, further showing that lower air temperatures can lessen the physiological impact of extended exposure periods on abalone.…”
Section: Discussionsupporting
confidence: 89%
“…Few purging times are provided in literature for abalone species, although those that include purging times prior to experimentation, involving transport, report a purging period of 2-3 days (Bubner et al, 2009;Sales, 2001). Based on this study the recommended purging times would be any time after the maximum GIE time was recorded in relation to both temperature and age (Figs.…”
Section: Tablementioning
confidence: 97%
“…Supplemental oxygen and ice packs for temperature regulation have also improved survival rates (Bubner et al . ; Buen‐Ursua & Ludevese ). Changes in temperature during live transport would be expected to have similar effects as it does in water, that is changes in metabolic rate, growth rate, anaerobic metabolism, cellular damage, immune function, etc.…”
Section: Physiological Response To Farmingmentioning
confidence: 99%
“…Firstly, animals are starved for 2-3 days to prevent defecation (Sales & Britz 2001), but there is also evidence that starved abalone survive better than fed animals (Watanabe et al 1994). Supplemental oxygen and ice packs for temperature regulation have also improved survival rates (Bubner et al 2009;Buen-Ursua & Ludevese 2011). Changes in temperature during live transport would be expected to have similar effects as it does in water, that is changes in metabolic rate, growth rate, anaerobic metabolism, cellular damage, immune function, etc.…”
Section: Air Exposurementioning
confidence: 99%